Peripheral Blood Smear Atypical Lymphocytes Association With Covid-19 Mortality - Nazir, Imran; TA, Gamal Ebid; Khalil, Khalid; Imran, Iffat; Almatrafi, Mohammed A; Muddassir, Rabia; Mutairi, Bader Al; Abouelregal, Tarek Elsayed (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: COVID-19 disease is currently pandemic, and its prevalence in Saudi Arabia is concerning. The SARS-CoV-2 virus primarily affects the lungs, but it also affects the haematopoietic system. The atypical lymphocytes on peripheral blood film that have a distinct morphological appearance were of particular interest in this study. Our goal was to see a link between atypical lymphocytes and COVID-19 patient mortality. Methods: This four-month single-centered prospective descriptive study was conducted in Makkah, Saudi Arabia. COVID-19 patients of both genders were randomly selected based on inclusion criteria. The data from the patient’s electronic medical record was extracted. All patients’ peripheral blood film parameters were recorded on days 3, 7, and 14 after admission. The statistical data was analysed using SPSS version 23. The Fisher’s exact test was used to determine the relationship with mortality. A p value of 0.05 was considered significant. Results: The total number of cases enrolled in the study was 226. The patients’ average age was 58 years (SD 0.5289). On the third day of admission, 88.2 % of patients with COVID-19 had atypical lymphocytes, with a mean of 2.35 ± 0.927. A significant correlation (p < 0.001) exists between atypical lymphocytes decreasing percentage number on the 3rd, 7th, and 14th days of admission and death. Conclusion: The decrease in the number of atypical lymphocytes on peripheral blood film has a significant association with the patients’ mortality. This fact can be used to develop a tailored management strategy based on the observation of peripheral blood film.